Integrasi Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK) dalam Manajemen Puskesmas di Puskesmas Sidomulyo Kota Pekanbaru Riau Tahun 2023 - Anna, Deddy; Harnani, Yessi; Marlina, Hastuti; Dewi, Oktavia; Ennimay, Ennimay (LPPM Hang Tuah Pekanbaru, 2024)
The Healthy Indonesia Program with a Family Approach (PIS-PK) integrates program implementation through an approach of 6 main components in strengthening the health system (Six building blocks), namely health service efforts, availability of health workers, health information systems, access to the availability of essential medicines, financing and government leadership. Indonesia Health Program with Family Approach (PIS-PK) is a program that focuses on strengthening basic quality health through a family approach. However, its implementation is not easy because it requires strong motivation and adequate infrastructure. The purpose of the research was to determine the integration of the PIS-PK program in the management of Sidomulyo Community Health Center, Pekanbaru City. Method: The research used a qualitative research design with phenomenological approach. Participants consist of 7 people with interviews conducted since August 2023. Results of the research planned input stage P1 were limited because of a lack of human resources, inconsistent data input and entry and unclear sources of funding plans, difficult process for implementation of P2 intersectoral such as adjusting schedules with stakeholders and meeting target families because they were rarely at home and P3 monitoring, control and assessment was limited infrastructure and facilities such as a small number of computers, frequent interruptions of applications, and inadequate interventions. It is hoped that the health community centre to add human resources, and infrastructure and establish partnerships to complete the PIS-PK roadmap.